The Grand Design by Stephen Hawking and Leonard Mlodinow - Regmi, Jeevan (Himalayan Physics, 2011)
The Grand Design by Stephen Hawking and Leonard Mlodinow Bantam Books on 2011. ISBN0553805371. The Himalayan Physics Vol.2, No.2, May, 2011 Page: 84-86 Uploaded Date: 1 August, 2011